KEBEBASAN BERPENDAPAT DAN PELANGGARAN HAK ASASI MANUSIA DI MEDIA SOSIAL - Dewi, Vebrika Dwi Purnama (Legal Studies Journal, 2024)
Freedom is defined as a fundamental human right and is guaranteed in the Indonesian constitution, including in the realm of social media. In the digital era, social media has become a broad space for expression, but it also presents challenges such as hate, hatred, defamation and the spread of misinformation. This research aims to analyze the legal protection of freedoms put forward in accordance with Law Number 19 of 2016 concerning ITE, which still focuses on prohibitions without providing clear protection for users. The research method uses a normative approach with analysis of statutory regulations and legal doctrine. The research results show that regulations related to freedom of expression on social media do not fully protect users’ rights. As a rule of law, Indonesia is obliged to provide concrete and balanced regulations to ensure freedom of expression remains responsible, maintains social ethics, and supports healthy democracy.